Pengaruh Kepemimpinan, Kompensasi Finansial Dan Lingkungan Kerja Fisik Terhadap Semangat Kerja Karyawan Pada CV. Leo Silver Batuyang Gianyar - Dharmawan, I Gede Arya Putra; Sudharma, I Nyoman (E-Jurnal Manajemen, 2013)
This research is done intent to know leadership role, financial compensation and physical work condition to is ardour employee job CV. Leo Silver Batuyang Gianyar. Job spirit constitute mental attitude of individual and also group who can push their to collaborate deep solve that task minimizes keliruan aught. There is linear regression even bifilar tech análisis data that is utilized in this research. analisis's result points out leadership, financial compensation and influential physical work condition simultan and partial to is ardour employee job. Financial compensation becomes influential variable dominant to is ardour employee job because base count Standardized Coefficients is Beta having supreme point which is as big as 0,428 than variable leadership and physical work conditions.